A metaphor analysis on students' perceptions of elderly living in nursing home - Emel, Bahadır Yılmaz (Magyar Gerontológia, 2023)
Aim It is aimed to evaluate the perceptions of nursing and midwifery students about the elderly living in nursing homes by metaphor analysis.